PELIBATAN STAKEHOLDERS DALAM PROSES INPRES MORATORIUM IZIN PERKEBUNAN SAWIT 2016-2017: SEBUAH TINJAUAN STAKEHOLDER-BASED POLICY PUBLIC PROCESS - Riaty Raffiudin (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2017)
This article discusses the involvement of stakeholders in the process of Instruksi Presiden Moratorium for palm oil plantation permits between 2016 and 2017 using the stakeholder-based public policy process from Altman and Petkus (1994) to answer the research question that has been posed, which is,